Effect of aerobic and resistance exercises on body composition and quality of life in overweight and obese women: a randomized control trial - GÜNER ÇİÇEK; Rabia Hurrem OZDURAK SINGIN (Faculty of Medicine, Universitas Trisakti, 2023)
BackgroundObesity has become a major health issue in the world and directly reduces the quality of life. The aim of this study was to compare the effect of aerobic and resistance exercises on body composition and quality of life (QoL) in overweight and obese women. Method An experimental study involving 90 overweight/obese women aged between 20-45 years participated in the study voluntarily and were randomized into control (n=30), aerobic exercise (AE) (n=30), and resistance exercise (RE) (n=30) groups. Either AE or RE groups performed exercise for 60 minutes per day for 10 weeks, whereas the control group did not perform any exercise. The body composition and QoL of the women were measured before and after the exercise. ResultsBody weight, BMI, fat mass, and waist and hip circumferences decreased significantly in both AE and RE groups after the exercise intervention compared to the control group (p<0.05). In addition, quality of life sub-dimensions including physical health, psychological health, social relationship, and environment sub-dimensions improved significantly in the AE and RE groups compared to the control group (p<0.001). Post hoc Tukey test showed that AE was as effective as RE for improving body composition parameters and QoL sub dimension compared to control group. ConclusionThis study demonstrated that both AE and RE were effective in improving body composition and thereby increasing the QoL in overweight and obese women. Both AE and RE programs are effective and should be considered within any multicomponent therapy program in overweight and obese women.